Impact of pacing-related differences on clinical and echocardiographic outcomes after TAVR with SAPIEN-3 valve. (14th October 2021) - Lak, H; Sammour, Y; Chawla, S; Gajulapalli, R D; Kumar, A; Parikh, P; Svensson, L G; Harb, S; Tarakji, K; Wazni, O; Reed, G W; Puri, R; et al.
Abstract: Background: Data regarding the impact of pacing on outcomes after transcatheter aortic valve replacement (TAVR) is evolving especially with regards to pre-existing PPM. We examined the impact of new and prior PPM on clinical and hemodynamic outcomes after SAPIEN-3 (S3) TAVR. Methods: Consecutive patients who underwent transfemoral-TAVR using S3 valve between April 2015 and December 2018 at our Clinic were included. Results: Among 1028 patients, 10.2% required new PPM within 30 days, while 14% had pre-existing PPM. The presence of either prior or new PPM had no impact on 3-year mortality (log-rank p=0.6), or 1-year major adverse cardiac and cerebrovascular event (MACCE) (log-rank p=0.65). New PPM was associated with lower left ventricular ejection fraction (LVEF) at both 30 days (54.4±11.3% vs. 58.4±10.1%; p=0.001), and 1 year (54.2±12% vs. 59.1±9.9%; p=0.009) compared to no PPM. Similarly, prior PPM was associated with worse LVEF at 30 days (53.6±12.3%; p<0.001) and 1 year (55.5±12.1%; p=0.006) compared to no PPM. Interestingly, new PPM was associated with lower 1-year mean gradient (11.4±3.8 vs. 12.6±5.6 mmHg; p=0.04), and peak gradient (21.3±6.5 vs. 24.1±10.4 mmHg; p=0.01) despite no baseline differences. Prior PPM was also associated with lower 1-year mean gradient (10.3±4.4 mmHg; p=0.001), and peak gradient (19.4±8 mmHg; p<0.001), and higher doppler velocity index (0.51±0.12 vs. 0.47±0.13; p=0.039). Moreover, 1-year LV end-systolic volume (LVESVi) was higher with new (23.2±16.1 vs. 20±10.8 ml/m 2 ; p=0.038), and prior PPM (24.5±19.7; p=0.038) compared to no PPM. Prior PPM was associated with higher moderate-to-severe tricuspid regurgitation (35.3% vs. 17.7%; p<0.001). There were no differences with regards to the rest of the studied echocardiographic outcomes at 1 year. Conclusion: In this S3 cohort, new and prior PPM did not affect 3-year mortality or 1-year MACCE, however they were associated with worse LVEF, higher LVESVi and lower mean and peak gradients on follow-up compared to no PPM. FUNDunding Acknowledgement: Type of funding sources: None.